Метафорика образа врага в прозе Ф. Гладкова 1920–1930-х годов - Демина, Е.Г. (Культура народов Причерноморья, 2014)
В статье анализируются художественные средства изображения врага и дополняются
новыми наблюдениями выводы современных исследователей о характерном для соцреализма 1920–1930-
х годов – так же, как и для стиля большевистской риторики в целом, – уподоблении классовой борьбы
войне тьмы и света. Рисуя вооруженного врага в «Цементе», Ф. Гладков прибегает к приему
расчеловечивания, обезличивания персонажа. В образе побежденного врага доминируют мотивы
деградации, болезни, разложения, смерти. Основные источники образности в изображении
политического противника у Ф. Гладкова – народная демонология и Библия. Фундаментальная
символика (бесы – свиньи) соседствует у писателя с пропагандистскими клише (бешеные псы). У статті проаналізовано художню специфіку втілення образу ворога у творах Ф. Гладкова.
висновки сучасних дослідників доповнюються новими спостереженнями щодо характерного для
соцреалізму 1920-1930-х років, власне, як і для стилю більшовицької риторики в цілому уподібненні
класової боротьби війні темряви і світла. Змальовуючи озброєного ворога в «Цементі», Ф. Гладков
залучає прийом знелюднення, знеособлення персонажу. В образі переможеного ворога домінують
мотиви деградації, хвороби, розкладання, смерті. Основні джерела образності в зображенні
політичного противника у Ф. Гладкова - народна демонологія й Біблія. Фундаментальна символіка (біси
- свині) у письменника стоїть поряд із пропагандистськими кліше (скажені пси). In the article artistic means for imaging enemy are analyzed and the conclusions are supplemented
by new observations of modern researchers dealing with obvious features in social realism of 1920s-1930s, as
well as in the style of “Stalin's writer” and the Bolshevik rhetoric in general – assimilation of the class struggle.
Depicting an armed enemy in “Cement”, F. Gladkov uses the technique of dehumanization, depersonalization of
the character emphasizing the beast in his image. In “Cement” and “Energy” vermin are hidden at the plant
management – they are either somebody inherently inanimate (“neat dummies”, “wax figures of the
panopticon”, “stuffed beings”, “pale masks”) or physical freaks (one of them has a eunuch face, another – “a
double skull”), necrophilia motif can be heard from the characterization of some heroes.
“New Land” is particularly rich in chthonic symbolism where vermin women are depicted as witches, demons,
rabid dogs. The main feature of non-human-enemies in “Energy” and “New Land” is the magical ability to
direct primal fear to others that only can be protected by collective vigilance.
The main sources of imagery in depicting a political opponent by F. Gladkov are folk demonology and the Bible.
The fundamental symbols (devils – pigs) adjoin propaganda clichés (mad dogs).